Addition of high-intensity interval training to a moderate intensity continuous training cardiovascular rehabilitation program after ischemic cerebrovascular disease: A randomized controlled trial - Lapointe, Thalia; Houle, Julie; Sia, Ying-Tung; Payette, Marika; Trudeau, François (Frontiers in Neurology, 2023)
Introduction Moderate intensity continuous training (MICT) is usually recommended for stroke or transient ischemic attack (TIA) patients. High intensity interval training (HIIT) has emerged as a potentially effective method for increasing cardiorespiratory fitness (CRF) among clinical populations. Its effectiveness remains to be demonstrated after stroke. A combined program of HIIT and MICT was designed to create a realistic exercise program implemented for a clinical setting to help patients become more active. Purpose This study aimed to compare the effects of a 6-month exercise program with either MICT only or a combination of HIIT and MICT and a control group in terms of CRF, cardiovascular risk factors, functionality, cognitive function (Montreal Cognitive Assessment) and depression markers (Hospital Anxiety and Depression Scale). Methods This randomized controlled trial started with 52 participants (33 men and 19 women, mean age: 69.2 ± 10.7) divided into three groups: HIIT + MICT combined, MICT, and control. Both exercise groups consisted of 4 weekly sessions including supervised and at-home exercise. Outcomes were assessed at T0 (baseline measure), T6 (end of exercise protocols), and T12 (follow-up), 40 participants having completed the 12-month follow-up. Results At T6, both HIIT+MICT and MICT programs provided a similar increase of CRF (3 ml·min-1·kg-1) from baseline (p < 0.01), while the control group showed a global slight decrease. Despite some decrease of CRF at T12 compared to T6, improvement persisted 6 months post-intervention (HIIT + MICT: p < 0.01 and MICT: p < 0.05). The control group decreased compared with baseline (p < 0.05). The two exercise programs induced a comparable increase in self-reported physical activity and a decrease in anxiety and depression markers. Participants in HIIT + MICT and MICT programs declared a good degree of acceptability assessed by the Acceptability and Preferences Questionnaire. Conclusion A 6-month HIIT + MICT combined program and a standard MICT program induced similar improvements in CRF, self-reported physical activity and anxiety and depression markers among patients with prior ischemic stroke or TIA compared with a control group. These effects appear to persist over time. Addition of HIIT was safe and considered acceptable by participants. Our results do not support any superiority of the combination HIIT + MICT nor disadvantage vs. MICT in this population.